Estrategias de acompañamiento remoto utilizadas por docentes practicantes, en instituciones del Modelo de Servicio Educativo Flexible, Trujillo-2021 - Contreras Bailón, Nattaly Milagritos (2022)
The purpose of this research was to study the level of development of remote accompaniment strategies used by teachers in institutions of the Flexible Educational Service Model, which were developed in Trujillo, using two surveys and a checklist proposed by the authors, which made it possible to evaluate the levels of development of remote accompaniment strategies in four dimensions: group activity, family counselling, family accompaniment, and meetings with parents. The interview and content analysis were the techniques applied to a sample of ten trainee teachers belonging to the 10th cycle of the Early Education course at the National University of Trujillo and to 22 parents participating in the Flexible Educational Service Model, where the result was that 100% were found to be at an achieved level, The main conclusion reached by this simple descriptive research was that it demonstrated a high level of effectiveness in the development of the strategies, which motivated a complete description of the forms of work developed within the Flexible Educational Service Model, which demonstrated effective work for the integral development of the children, with the families as a strategic ally.